Lean Manufacturing: Waste Reduction Using Value Stream Mapping - Zahrotun Nihlah; Taufiq Immawan (E3S Web of Conferences, 2018)
Cristal Sri Sujarwati is a small medium enterprise (SME) that produce keripik salak in Sleman, Yogyakarta. To survive and win industrial competition, Cristal Sri Sujarwati was required to improve its performance. But in reality there was a lot of waste in order fulfillment processes marked by ineffective and inefficient work. In this research, lean manufacturing aims to identify and eliminate waste so that the company could improve its performance in winning the industry competition. Lean manufacturing is a systematic approach used to identify and eliminate waste. This lean concept could improve responsiveness through waste reduction, continuous improvement and cost reduction. In order to identify and eliminating waste, a value stream mapping tools, waste weighting questionnaire, value stream analysis tools, and fishbone diagram are used. From the results of research, the dominant waste in the production process was waste defects, waiting, and unnecessary inventory. To eliminate waste, process activity mapping (PAM), the one of detailed mapping tools in VALSAT are used. From the results of the improvement recommendations analysis, lead time decreased by 80 minutes. From the analysis using PAM, there was a reduction of NVA activity from 3.10% to 1.01%.